Agricultural policy, development ans international trade: Consultant final report IICA/EMBRAPA-PROCENSUL II Trade liberalization and other desirable agricultural policy - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2021)
48 páginas.